One size fits all? The effects of teacher cognitive and non-cognitive abilities on student achievement - Erik Grönqvist; Jonas Vlachos (Institute for Labour Market Policy Evaluation (IFAU), 2008)
Teachers are increasingly being drawn from the lower parts of the general ability distribution, but it is not clear how this affects student achievement. We track the position of entering teachers in population-wide cognitive and non-cognitive ability distributions using school grades and draft records from Swedish registers. The impact on student achievement caused by the position of teachers in these ability distributions is estimated using matched student-teacher data. On average, teachers' cognitive and non-cognitive social interactive abilities do not have a positive effect on student performance. Howÿever, social interactive ability turns out to be important for low aptitude students, whilst the reverse holds for cognitive abilities. In fact, while high performing students benefit from high cognitive teachers, being matched to such a teacher can even be detrimental to their lower performing peers. Hence, the lower abilities among teachers may hurt some students, whereas others may even benefit. High cognitive and non-cognitive abilÿities thus need not necessarily translate into teacher quality. Instead, these heteroÿgeneities highlight the importance of the student-teacher matching process.
Keywords: I21; H4; J4; 330; Cognitive and non-cognitive ability; Teacher quality; Student achievement; Lehrkräfte; Kognition; Schüler; Bildungsniveau; Schweden